Police and policing in India : voices of officers - Barua, S. K. (Samir K.) ([London] : SAGE, 2016)
The case provides an opportunity to discuss the state of policing as a service in India. It contains a short review of key reports that have been brought out over the years on reforms needed in policing in India to make police a force that is responsive to the needs of the society.
Originally Published in: Barua, S. K. (2013). Police and Policing in India: Voices of Officers. PSG0113. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Police administration -- Case studies; Police -- India -- Case studies; Organizational behavior -- Case studies; Service industries -- Case studies